ABOLITION OF NATURAL LIFE SENTENCE IN MALAYSIA: A CRITICAL ANALYSIS - Moin Uddin (Journal of Malaysian and Comparative Law, 2025)
A natural life sentence is a severe punishment in which prisoners remain in prison until death. This sentence is used as an alternative to the death penalty in exceptional situations which do not mandate the punishment of death. In Malaysia, the Court was empowered by the law till 3rd April 2023 to impose a natural life sentence in the criminal justice system based on Section 130A(f) of the Penal Code. This law aroused the vexed issue that a natural life sentence does not achieve the purposes of sentencing in the criminal justice system. In addition, a natural life sentence violates human rights laws as it is inhumane or degrading to the accused. This paper aims to critically analyse and examine the rationales and consequences of imposing a natural life imprisonment. The qualitative research method has been used in gathering and analysing data. This study concludes that a natural life sentence contradicts human rights, fails to achieve public interest, violates the freedom and dignity of the prisoners, and also fails to attain penological goals. This research suggests that the natural life sentence should be abolished around the world with an option of parole to establish human pride and dignity and protect the social and human rights of the prisoners.